Comparative Ecological Based Life Cycle Assessment of Multi- Crystalline PV Technology and Coal Electric Power - Lang, Benjamin; Halog, Anthony (Journal of Technology Innovations in Renewable Energy, 2015)
Multicrystalline (multi-Si) photovoltaic (PV) technology is increasingly common throughout Australia and the developed world, as renewable energy technologies become viable electrical generation alternatives to coal and nuclear power. We have examined the cradle-to-grave life cycle of a 3kWp multi-Si PV system within Australia. The highest contribution of environmental impacts results from the usage of fossil fuel energy resources and their emissions at the pre-production and manufacturing stages. We analyze the impacts of multi-Si technology on ecosystem goods and services (EGS) and compared it with impacts resulting from coal power electricity. For 3kWp multi-Si system, coal, crude oil and iron ore were the critical resources consumed from the lithosphere while the public supply of water was consumed from the hydrosphere. For coal power electricity, coal and water were the resources most consumed from both the lithosphere and hydrosphere. However the resource consumption from coal power electricity is significantly larger than that of multi-Si PV. Coal power electricity is also responsible for much greater energy and exergy consumption compared to multi-Si PV. The main ecosystem disturbances resulting from the lifecycle of a 3kWp multi-Si unit affect supporting and regulating services though these disturbances are considerably lower than the services impacted from coal power electricity. The study concludes that similar analysis performed on another PV technology would provide a greater understanding to the Eco-LCA results for multi-Si PV technology, particularly with relation to exergy analysis.